MEDIATION AGREEMENT (Eureka Journal of Education & Learning Technologies, 2026)
A mediation agreement is essentially a way to quickly and clearly resolve disputes arising in a legal relationship at the request of both parties. In this case, mediation agreement is mainly used in civil and economic legal relations. That is, the convenience of simplifying the work of the court and not wasting time should not be overlooked. The parties using this method should reach a mutually acceptable solution with the mediator without going to court. This type of agreement is voluntary. Here, the responsibility of the mediators is significant, as their duty is to resolve the issue peacefully and irrevocably. The legislation and concepts of the French state regarding the mediation agreement.
Keywords: Mediation, mediation agreement, mediator, principles, Ministry of Justice, register, vocational education, participants in mediation and their rights and obligations, requirements for the mediator and their responsibilities, suspension and reinstatement of the mediator's activities, on mediation in France.